Hierarchical linear modeling for determining the effect of ICT literacy on mathematics achievement - Suci Paramitha Liestari; Muhardis Muhardis (REID (Research and Evaluation in Education), 2021)
This study aims to identify the effect of ICT literacy on mathematics achievement in grade 8 by using the Indonesian Student Competency Assessment's (Asesmen Kompetensi Siswa Indonesia or AKSI) 2019 questionnaire data. A multistage probability sample of 13,079 students was analyzed using a two-level hierarchical linear model (HLM) which student achievement scores are the first level laid in schools as the second level. The results of the analysis revealed that SES, the number of smartphones and computers that students have at home, the availability of ICT at home and school, the use of ICT for education, and perspective on the benefits of ICT in daily life have a positive influence on mathematics literacy achievement, while the easiness of access to the use of digital devices in schools has negative influence at the student level. At the school level, the high mathematics literacy achievement of students is influenced by the location of the school and the number of certified teachers. School accreditation and completeness of learning facilities in schools are not factors upon better students toward their mathematics literacy achievement. However, the interaction between the easiness of access to the use of digital devices in schools and the completeness of learning facilities in schools have an influence in increasing students' mathematics literacy achievement. Based on the diversity component, it is known that the diversity of students' mathematical literacy achievement explained by the student level and school-level variables are 33.24 and 0.18, respectively.